Minimally invasive osteosynthesis in fractures of extremities with combined trauma in children (Herald of the National Children's Medical Center, 2025)
Background. Improvement of treatment outcomes for fractures of the long bones of the extremities using minimally invasive osteosynthesis methods in combined trauma in children.Materials and methods. In the period from 2020 to 2024, 654 children with combined injuries of varying severity were treated at the Republican Scientific Center for Emergency Medical Care of the Ministry of Health of the Republic of Uzbekistan. Of these, 120 children were treated with a diagnosis of polytrauma with a predominance of skeletal injuries. 487 (74.5%) children were treated after an accident, 101 (15.4%) children fell from a height. he remaining 66 children (10.1%) received combined injuries of the musculoskeletal system as a result of domestic, street and sports injuries.Results. In our opinion, it is important to develop the possibility of performing single-stage operations (during one anesthesia) in specialized centers, such as the emergency medical center. Surgical interventions for a dominant injury are considered primary, and limb surgeries are performed in cases of massive bleeding, such as segment rupture. In other cases, staged operations are recommended.Conclusion. The use of simple, inexpensive metal structures for fractures of long bones in children with combined trauma, the use of minimally invasive osteosynthesis methods. Minimally invasive methods of osteosynthesis for fractures of the long bones of the extremities in children can be used both early and delayed, depending on the patient’s general condition.reet, and sports injuries.
Keywords: osteosynthesis; combined trauma; minimally invasive; plaster bandage; childhood trauma; fractures; electron-optical transducer